Measuring Spillovers of Venture Capital - Martin Watzinger; Monika Schnitzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this paper we measure knowledge spillovers arising from venture-capital nanced companies on the patenting activities of other companies and com- pare them to spillovers from established rms. We develop a novel measure to to identify the appropriate spillover pool based on backward citations which re ect channels for learning between rms. Using panel data of U.S. rms we show that venture capital investment in start-ups generates signi cant spillovers on the patent quantity and quality of other rms. Counterfactual estimates suggest that these spillovers are larger than those generated by corporate R&D. We address potential concerns about causality with an in- strumental variable strategy using changes in federal and state tax incentives as instrument for R&D and past fund raising as instrument for venture capital investment.
Keywords: O31; O32; G24; 330